Neonatal Cardiac Emergencies: A Multidisciplinary Simulation Curriculum for Neonatology and Pediatric Cardiology Fellows - M. Abigail Simmons; Andrea Otero-Luna; Brooke Redmond; John Fahey; Cheyenne Beach; Christie Bruno; Lindsay Johnston (Association of American Medical Colleges, 2020)
Introduction Although care for neonates with cardiac disease is frequently provided by neonatologists and pediatric cardiologists, training in the multidisciplinary management of neonatal cardiac emergencies is not often included in fellowship training. We created a multidisciplinary simulation curriculum to address the skills needed for neonatal cardiac care. Methods Neonatology and pediatric cardiology fellows participated in 1-hour simulations on 3 different days. They managed a neonate with: (1) cyanosis, (2) cardiogenic shock, and (3) an unstable arrhythmia. Using both remote consultation and bedside evaluation, the participants diagnosed and jointly established a management plan for the infant. During the debrief, facilitators reviewed the clinical decisions and multidisciplinary management skills of the participants. Participants completed pre- and postparticipation surveys to evaluate the curriculum's effect on their confidence in the management of neonatal cardiac disease. Results Thirty-three paired survey responses from 20 participants (11 neonatology and 9 pediatric cardiology) reported a mean overall satisfaction score of 4.6 (SD = 0.7) based on a 5-point Likert scale. Postparticipation confidence scores improved significantly in: (1) the recognition of the signs of congenital heart disease (pre = 4.1, post = 4.5, p = .01), (2) differentiation of cardiac cyanosis from noncardiac cyanosis (pre = 3.9, post = 4.2, p = .05), and (3) confidence in discussing cardiac concerns with consultants (pre = 3.3, post = 4.1, p = .02). Discussion This multidisciplinary simulation improved fellows' confidence in the management of neonates with cardiac disease and provided an opportunity to practice team work, remote consultation, and cross-disciplinary communication.